2023
DOI: 10.1158/1538-7445.am2023-3423
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3423: NX-2127: A first-in-class clinical stage degrader of BTK and IKZF1/3 for the treatment of patients with B cell malignancies

Abstract: Chronic activation of Bruton’s Tyrosine Kinase (BTK) signaling is a hallmark of B cell malignancies. Over the last decade, covalent and reversible inhibitors of BTK have proven effective for the treatment of many of these including chronic lymphocytic leukemia, diffuse large B cell lymphoma, mantle cell lymphoma, marginal zone lymphoma and Waldenstrom macroglobulinemia. However, the long-term efficacy of BTK inhibitors has been limited by both tolerability and the emergence of acquired resistance mutations. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 89 NX-2127 is a novel oral BTK degrader that also degrades IKAROS family zinc finger 1 (IKZF1) and IKZF3, inducing immunomodulatory activity. 90 Recently, preliminary data of the phase 1 NX-2127-001 trial have been reported. Among 17 RR-CLL patients, all had received a prior BTKi and 13 patients (76.5%) had also received venetoclax.…”
Section: Novel Targeted Therapies For Double Refractory Diseasementioning
confidence: 99%
“… 89 NX-2127 is a novel oral BTK degrader that also degrades IKAROS family zinc finger 1 (IKZF1) and IKZF3, inducing immunomodulatory activity. 90 Recently, preliminary data of the phase 1 NX-2127-001 trial have been reported. Among 17 RR-CLL patients, all had received a prior BTKi and 13 patients (76.5%) had also received venetoclax.…”
Section: Novel Targeted Therapies For Double Refractory Diseasementioning
confidence: 99%